PENGARUH EKUITAS MEREK TERHADAP PENGGUNAAN MONITOR PASIEN MEREK PHILIPS DI JAKARTA - Nurdin, Taufik; Agustin, Prima Mulyasari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to find out how responses, consumer loyalty and brand equity influence consumer loyalty of Philips monitor patients. Questionnaire respondent data was obtained from end users, namely nurses who work in intensive care rooms in 5 vertical hospitals in Jakarta. The questionnaire was distributed directly to 185 respondents. Hypothesis for 3 hypotheses using SEM PLS analysis with SmartPLS 3. Testing consists of Outer Model, namely Convergent Validity Test, Discriminant Validity Test, Average Variance Extracted (AVE) Test, Composite Reliability Test, Cronbach Alpha Test, Inner Model and Bootstrapping. Test results show that H1: Brand awareness has a positive and significant effect on consumer loyalty. H2: Brand association has a positive and significant effect on consumer loyalty. H3: Perceived quality has a positive and significant effect on consumer loyalty. It is hoped that this research can provide input to companies as a strategy to increase consumer loyalty and can provide good benefits for further research.